The Methodology of al-Maturidi’s Qur’anic Exegesis: Study of Ta’wilat Ahl al-Sunnah - Ahmad Choirul Rofiq (Al-Jami'ah: Journal of Islamic Studies, 2009)
According to Islamic theology, al-Maturidi is one of the three prominent Muslim theologians of Ahl al-Sunnah wa al-Jama'ah who are called aqtab madhhab Ahl al-Sunnah wa’l-Jama‘ah (the leaders of Sunnite school of thought). In addition to his reputation as a theologian, al-Maturidi actually was competent in various Islamic sciences. In Quranic exegesis, he has Ta’wilat Ahl al-Sunnah or Ta’wilat al-Qur’an. Unfortunately, this fact isn't known well by Islamic researchers. This article is going to elucidate the features of his work that encompass at least seven characteristics. Al-Maturidi prefers to combine the naqli (traditional) and ‘aqli (rational) sources. Consequently, it can be identified as tafsir bi’l-izdiwaj or the exegesis that amalgamates tafsir bi’l-ma’thur (traditional exegesis) with tafsir bi’l-ra’y (rational exegesis). He is not an interpreter who uses excessive grammatical analysis to interpret the Qura'nic verses. He sometimes presents many styles of qira’ah (recitation of the Qur'an) without thorough explanation. He almost never uses Isra’iliyyat (the Judeo-Christian traditions and tales) to interpret the Qura'nic verses. He favors tawassut (nonaligned and independent standpoint) when he deals with different viewpoints among theologians. He tends to follow the Hanafite school of thought in discussing the jurisprudential Qura'nic verses. He applies asbab al-nuzul (the causes of revelation) loosely.